Multiple sclerosis and risk of attempted and completed suicide – a cohort study. (27th April 2016) - Brenner, P.; Burkill, S.; Jokinen, J.; Hillert, J.; Bahmanyar, S.; Montgomery, S.
Abstract : Background and purpose: Patients with multiple sclerosis (MS) are known to have an elevated suicide risk, but attempted suicide is incompletely investigated. The relation between education level and suicidality has not been investigated in MS patients. Our objective was to estimate attempted suicide and completed suicide risks amongst MS patients. Methods: A total of 29 617 Swedish MS patients were identified through the Swedish Patient Register and matched with 296 164 people without MS from the general population. Cox regression analysis estimated hazard ratios (HRs) with 95% confidence intervals (CIs) for the association of MS with attempted and completed suicide, with adjustment for age, sex, education and calendar period. Results: The adjusted HR for attempted suicide amongst MS patients is 2.18 (95% CI 1.97–2.43) compared with the general population cohort. For completed suicide the HR is 1.87 (95% CI 1.53–2.30). In both groups women are at higher risk of attempting suicide, whilst men are at higher risk of completing suicide. Education level is inversely associated with completed suicide amongst the non‐MS cohort (0.68, 0.51–0.91), but not amongst MS patients (1.10, 0.60–2.04). Conclusion: Multiple sclerosis patients are at higher risk of both attempted and completed suicide. No evidence was found of an inverse association between educational level and risk of completed suicide amongst MS patients.